Endolysins against Streptococci as an antibiotic alternative - Wong, Kuan Yee; Megat Mazhar Khair, Megat Hamzah; Song, Adelene Ai-Lian; Masarudin, Mas Jaffri; Chong, Chou Min; In, Lionel Lian Aun; Teo, Michelle Yee Mun (Frontiers in Microbiology, 2022)
Multi-drug resistance has called for a race to uncover alternatives to existing antibiotics. Phage therapy is one of these explored alternatives, including the use of endolysins, which are phage-encoded peptidoglycan hydrolases responsible for bacterial lysis. Endolysins have been extensively researched in different fields, including medicine, food and agricultural applications. While the target specificity of various endolysins varies greatly between species, this current review focuses specifically on streptococcal endolysins. Streptococcus spp. causes numerous infections, from the common strep throat to much more serious life-threatening infections such as pneumonia and meningitis. It is reported as a major crisis in various industries, causing systemic infections associated with high mortality and morbidity as well as economic losses, especially in the agricultural industry. This review highlights the types of catalytic and cell wall binding domains found in streptococcal endolysins and gives a comprehensive account of the lytic ability of both native and engineered streptococcal endolysins studied thus far, as well as its potential application across different industries. Finally, it gives an overview of the advantages and limitations of these enzyme-based antibiotics, which has caused the term enzybiotics to be conferred to it.